ChemInform Abstract: Total Synthesis and Structure Determination of JBIR‐108 — A 2‐Hydroxy‐2‐(1‐hydroxyethyl)‐2, 3‐dihydro‐3(2H)‐furanone Isolated from Streptomyces gramineus IR087Pi‐4. Issue 21 (May 2015) - Fujiwara, Koichi; Tsukamoto, Hirokazu; Izumikawa, Miho; Hosoya, Takahiro; Kagaya, Noritaka; Takagi, Motoki; Yamamura, Hideki; Hayakawa, Masayuki; Shin‐ya, Kazuo; Doi, Takayuki
Abstract Natural JBIR‐108 is shown to be a mixture of the major diastereomer (Ia) and the minor diastereomer (Ib).